MOLECULAR DOCKING OF HYRTIMOMINE A-K FROM MARINE SPONGE HYRTIOS SPP. AS ANTICANCER TARGET OF PHOSPHOINOSITIDE-DEPENDENT KINASE 1 - RAMA ADIGA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The hyrtimomine A-K class of indole-based compounds extracted from Hyrtios spp. of sponges from the sea has not been studied for their anticancer properties. Phosphoinositide-dependent kinase 1 (PDK1) is a master regulator of many types of cancer. Compounds currently targeting PDK1 are currently of poor specificity and solubility. Hence, molecular docking to look for new compounds inhibiting PDK1 from the marine environment was carried out. Methods: Target selection for ligands hyrtimomine A-K was done using PharmMapper tool. Molecular docking was done using iGEMDOCK 2.1, a generic evolutionary method of docking. Site moiety mapping was done in SimMap to extract the anchor preference of the top hits. Comparison of ligand binding energies, pharmacokinetic properties with lead compound BX-517 was carried out. Results: Hyrtimomine B, C, D, and G were top hits using iGEMDOCK. The highest score was obtained for hyrtimomine C. Van der Waals interaction at T222 and V96 and hydrogen bond interaction at K111 determined pocket stability. The solubility properties of the compound showed higher score for hyrtimomine C. The conserved features of hyrtimomine C were then compared with the crystal structure of lead compound (BX-517, which was not developed further due to poor solubility and bioavailability). The pharmacokinetic properties of hyrtimomine C were superior to BX-517 and had better solubility and drug-likeness score, hence, may be a candidate structure for drug development. Conclusion: The unique azapeno indole structure of hyrtimomine C highlighted the mode of binding and residues in binding site.